Coexisting vulvar paget's disease and mucinous carcinoma of the breast: A case report and review of the literature - Rangsima Aroonroch (2018)
Vulvar Paget' disease is the most common site of extramammary Paget's disease (EMPD). The disease frequently associated with the underlying invasive skin adnexal carcinoma or representing the migration of underlying internal malignancy, especially anorectal and genitourinary cancer, but the coexisting with primary breast cancer is rare. Herein, the authors report a case of a 46-year-old Thai woman who had vulvar Paget's disease with subsequent development of mucinous carcinoma of the breast. Interestingly, the overexpression of HER-2/neu in vulvar Paget's disease raises the additional option of anti-HER-2/neu antibody therapy in highly aggressive or recurrent disease. In conclusion, primary breast cancer should be of concern in patients with vulva Paget's disease, even though it is an uncommon association.